Abiotic Stress Effects on Plants under Climate Change - Bishnoi, Subodh Kr.; Chauhan, R. P. S.; Yadav, Naresh Kr.; Bishnoi, Pooja (International Journal of Bio-resource and Stress Management, 2017)
Abiotic stress is a stress that occurs as a result of damage done to plants by non-living and often tangible factors such as intense sunlight, wind etc. This naturally occurring stress is most detrimental to plant health when it influences the environment beyond its normal range of variation. Since abiotic stresses originate from surrounding environment therefore, these are more harmful for plants than animals as plants are dependent on environmental factors. Research has also shown that abiotic stressors are at their most harmful when they occur together, in combinations of abiotic stress factors. Extended exposure to extreme temperatures, high salinity, etc results in certain physiological and biochemical changes in plants that adversely affect the growth and productivity of crops worldwide. Plant biodiversity is determined by many things, and one of them is abiotic stress. If an environment is highly stressful, biodiversity tends to be low. If abiotic stress does not have a strong presence in an area, the biodiversity will be much higher. This means that species are more likely to become plants population threatened, endangered, and even extinct, when and where abiotic stress is especially harsh. Thus, abiotic stress leads to altered metabolism and damage to bio-molecules and is responsible for reduced yield in several major crops. In this review, we summarize recent progress on systematic analysis of plant responses to abiotic stress. Abiotic stresses are serious threats to agriculture and the environment which have been exacerbated in the current century by global warming and industrialization.